The Challenges and Opportunities in Opening Indonesian Language Education Study Program at UIN Antasari Banjarmasin - Nida Mufidah; Afifah Linda Sari (Dinamika Ilmu, 2022)
Indonesian is well-known, and it is taught at institutions across the world, including Australia. This study aims at describing prospective students, teachers, lecturers,' practitioners, and the general public's reactions to the Indonesian Language Education Study Program at the Faculty of Tarbiyah and Teacher Training of UIN Antasari Banjarmasin and identified data will be described as findings and discussed using Morrison's theory of needs analysis profile for the program readiness. A survey is used in this investigation. The questionnaires and interviews in this research were both open-ended. The technique used is a questionnaire technique using Google Forms by distributing questionnaires directly to respondents, namely 173 prospective students were class XII high school students, 24 were Indonesian language teachers, and 104 were education practitioners, lecturers, supervisors, and members of the community from several districts and cities in South Kalimantan. The plan to launch the Indonesian Language Education Study Program at UIN Antasari Banjarmasin received a positive reaction from many stakeholders and will be implemented immediately. Graduates of this degree may become professional educators with Islamic perspectives and Indonesian language teachers for international and national schools, as well as Indonesian for foreign speakers with distinctive qualities. Before a new study program starts, educators, teaching staff, and infrastructure must all be carefully prepared, as must the program's documentation. Therefore, the result of this study is expected to be the consideration by the university for opening the Indonesian Language Education Study Program at UIN Antasari Banjarmasin.